Geographic variation in heart failure with reduced ejection fraction: insights from the VICTORIA trial. (3rd October 2022) - Tsutsui, H; Lam, C S P; Zhang, J; Godoy-Palomino, A; Tziakas, D; Cohen-Solal, A; Freitas, C; Patel, M J; Ezekowitz, J A; Hernandez, A F; Pieske, B; O'Connor, C M; et al.
Abstract: Background: Geographic differences and background therapy have not been explored in the global VICTORIA trial, which enrolled high-risk patients with recent worsening heart failure with reduced ejection fraction (HFrEF). Methods and results: Among 5050 patients enrolled in 5 pre-specified geographic regions, 34% were from Eastern Europe, 18% Western Europe, 23% Asia Pacific, 14% Latin and South America, and 11% North America (Table 1). Patients from Western Europe were older, had more atrial fibrillation, and lower glomerular filtration rates. Patients from Eastern Europe had more coronary artery disease and exhibited more advanced symptoms (∼50% New York Heart Association [NYHA] class III), whereas those from Latin and South America were less symptomatic (∼70% NYHA class II). North American patients had the largest body mass index as well as more diabetes and hypertension. Levels of NT-proBNP at randomization and MAGGIC risk scores were highest in Western European patients. Evidence-based triple medication therapy was used most frequently in Latin and South America and less frequently in North America; conversely, cardiac resynchronization therapy and implantable cardioverter defibrillators were most frequently used in North America and least frequently in Latin and South America. The overall primary composite event rate (cardiovascular death or HF hospitalization) in the placebo arm was 36.6/100 person-years over a median of 10.8 months and after adjusting for the MAGGIC score. When examined by region, these event rates were nominally highest in North America and lowest in Western Europe. Conclusion: Substantial regional differences exist in characteristics and treatments among patients in this global trial of patients with HFrEF and a recent worsening event. These findings demonstrate the continuing unmet needs and opportunities for enhancing care in HFrEF. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): VICTORIA was funded by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA and Bayer AG, Wuppertal, Germany.